Teacher's Bilingual Strategies (English-Indonesian) in Teaching Vocabulary in EFL Classroom - Monige - (Loquen, 2026)
This study examines teacher bilingual strategies (English-Indonesian) in teaching vocabulary in EFL classrooms and their impacts on students’ vocabulary acquisition. Employing a qualitative descriptive design, the research was conducted at Sekolah Dasar Kristen 2 Rantepao (Sekolah Lentera Harapan Toraja), Toraja Utara, South Sulawesi, Indonesia, involving two grade V classes comprising 60 students as participants. Data were collected through video-audio classroom observation across multiple sessions and semi-structured interviews with the teacher and selected students. Data analysis followed the interactive model of Miles, Huberman, and Saldana (2019), encompassing data condensation, data display, and conclusion drawing. The findings reveal two principal results. First, the teacher employed multiple bilingual strategies-including brainstorming, demonstration, games, and review activities-with code-switching as the primary linguistic mechanism alternating between English and Indonesian. Both inter-sentential and intra-sentential code-switching types were identified across all strategy types. Second, the teacher’s bilingual strategies positively impacted students’ vocabulary acquisition by enhancing comprehension, increasing active participation, and facilitating productive vocabulary use in classroom interaction. Students consistently preferred the English-first, Indonesian-second instructional sequencing as it supported their understanding of new vocabulary items. The study contributes empirical evidence for the pedagogical value of strategic bilingual use in primary EFL classrooms and offers practical implications for EFL teacher education in multilingual Indonesian contexts.